2010
DOI: 10.1017/s0033291710001133
|View full text |Cite
|
Sign up to set email alerts
|

Vital exhaustion and cardiovascular prognosis in myocardial infarction and heart failure: predictive power of different trajectories

Abstract: Vital exhaustion and cardiovascular prognosis in myocardial infarction and heart failure Smith, O.R.F.; Kupper, N.; Denollet, Johan; de Jonge, P. General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
1
24
0
1
Order By: Relevance
“…The proportion of individuals classified as low-stable was 68%, which is towards the upper limit of the proportion observed in studies applying similar methods to other clinical populations [22][23][24][25][26][27][28][29][30]. This is not entirely surprising since, despite its impact on health-related quality of life, it seems unlikely that diagnosis of RA is potentially as traumatic an experience as a myocardial infarction or breast cancer surgery.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The proportion of individuals classified as low-stable was 68%, which is towards the upper limit of the proportion observed in studies applying similar methods to other clinical populations [22][23][24][25][26][27][28][29][30]. This is not entirely surprising since, despite its impact on health-related quality of life, it seems unlikely that diagnosis of RA is potentially as traumatic an experience as a myocardial infarction or breast cancer surgery.…”
Section: Discussionmentioning
confidence: 69%
“…In other words, most individuals can be seen as being "resilient" to the potential trauma caused by these conditions [29]. This is further supported by studies examining distinct trajectories of fatigue and vital exhaustion in individuals with heart failure [30,31].…”
Section: Introductionmentioning
confidence: 80%
“…Then there is care at admission, medication management [44] and associated costs-here the trajectory concept emerges. There is also an aspect regarding the effectiveness of the measures implemented [46][47][48][49][50][51][52] and the different treatments [53][54][55]. Another investigated aspect concerns lifestyle, with regard to dietary habits, healthy lifestyle [56], comorbidities [43,57] (smoking and/or alcohol), but also environmental factors like atmospheric pollution.…”
Section: Discussionmentioning
confidence: 99%
“…One study 14 examined different trajectories of VE over a period of 1 year and revealed that patients with increasing levels of VE had a higher risk of future adverse CVD events. Two studies examined the influence of a stress management program 15,16 on VE.…”
Section: Downloaded By [Kungliga Tekniska Hogskola] At 02:19 03 Octobmentioning
confidence: 99%